The ministry of ungentlemanly warfare [videorecording (DVD)] - Ritchie, Guy; Amel, Arash; Tamasy, Paul; Johnson, Eric (Screenwriter); Benstead, Christopher, 1981-; Cavill, Henry, 1983-; González, Eiza, 1990-; Ritchson, Alan, 1984-; Pettyfer, Alex, 1990-; Fiennes-Tiffin, Hero; Olusanmokun, Babs; Zaga, Henry, 1993-; et al. (Lionsgate, 2024)
The British military enlists a small group of highly skilled soldiers to launch an attack against German forces behind enemy lines during World War II.